2014
DOI: 10.1016/j.visres.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Obligatory averaging in mean size perception

Abstract: The perception of ensemble characteristics is often regarded as an antidote to an established bottleneck in focused attention and working memory, both of which appear to be limited in capacity to a few objects only. In order to test the associative law of summation, observers were asked to estimate the mean size of four circles relative to a reference circle. When there was no time to scrutinize each individual circle, observers discriminated the mean size difference identically, irrespective of whether the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 29 publications
4
37
0
Order By: Relevance
“…This finding is concordant with both the postperceptual role for color categories in cognition (He et al, 2014) and the early and automatic nature of ensemble encoding (e.g., Allik, Toom, Raidvee, Averin, & Kreegipuu, 2014;Corbett & Oriet, 2011; and also supports our previous findings of the effect of categories on mean color familiarity (Maule et al, 2014).…”
Section: Interim Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is concordant with both the postperceptual role for color categories in cognition (He et al, 2014) and the early and automatic nature of ensemble encoding (e.g., Allik, Toom, Raidvee, Averin, & Kreegipuu, 2014;Corbett & Oriet, 2011; and also supports our previous findings of the effect of categories on mean color familiarity (Maule et al, 2014).…”
Section: Interim Discussionsupporting
confidence: 91%
“…This is contrasted with the prediction regarding serial, focused attention on individual elements. A basic prediction of a focusedattention account is that, assuming the number of elements sampled is constant (but see Allik et al, 2014), averaging accuracy should decline with more elements as the subsample of elements to which attention is paid is more prone to bias. Marchant et al (2013) found that adding more elements decreased accuracy of mean settings for ensembles in which each element had a unique size.…”
Section: Exhaustive Processing Versus Subsamplingmentioning
confidence: 99%
See 1 more Smart Citation
“…When there were many items to be grouped into ensembles, it seems that the selection mechanism operated at ensembles level by allocating attention to the centroid of a set of multiple items. Therefore, the results of Experiment 2 not only verify that the centroid of a set of multiple items can serve as the focus of ensemble-based attention, but they also suggest that the centroids of ensembles can be extracted in a compulsive, obligatory manner to direct the deployment of attention, as are other ensemble feature of visual textures (Allik, Toom, Raidvee, Averin, & Kreegipuu, 2014;Oriet & Brand, 2013).…”
Section: Discussionmentioning
confidence: 66%
“…Although it was once suggested that sampling strategies of this kind might explain the performance of subjects in ensemble perception studies (e.g. Allik et al 2013Allik et al , 2014Marchant et al 2013), that view is now regarded as having been conclusively rebutted, for ensemble judgements are simply too accurate to be explained in terms of limited samples Utochkin and Tiurina 2014;Haberman and Whitney 2012;Brady and Alvarez 2015;Albrecht et al 2012).…”
Section: Is the Warrant For Ensemble Judgments Immediate?mentioning
confidence: 99%